Approaches to the therapy of heart failure with reduced ejection fraction. Resolution of an online meeting of the Volga Federal District experts - A. S. Galyavich; I. V. Fomin; I. R. Gaisin; F. V. Valeeva; N. G. Vinogradova; A. S. Salasyuk; E. I. Tarlovskaya; N. R. Khasanov; A. M. Shutov; E. N. Volodina; L. V. Grekhova; P. S. Guseva; et al. (Российский кардиологический журнал)
At an online meeting of experts held on May 14, 2021 additional research results on a sodium-glucose co-transporter-2 (SGLT2) inhibitor empagliflozin in patients with heart failure with reduced ejection fraction were considered. According to the data from the EMPEROR-Reduced international study, cardiovascular and renal effects of empagliflozin therapy in patients with and without type 2 diabetes (T2D) were analyzed. A number of proposals and recommendations was accepted regarding the further study of cardiovascular and renal effects of empagliflozin and its use in clinical practice in patients with heart failure, regardless of the T2D presence.